Impacts of Electrical Line Losses Comprising Mul-ti-Distributed Generation in Distribution System - Surakit Thongsuk; Atthapol Ngaopitakkul (My University, 2013)
This paper proposes to study the impacts of electrical line losses due to the connection of distributed generators (DG) to 22kV distribution system of Provincial Electricity Authority (PEA).Data of geographic information systems (GIS) including the distance of distribution line and location of load being key parameter of PEA is simulated using digital simulation and electrical network calculation program (DIgSILENT) to analyze power loss of the distribution system.In addition, the capacity and location of DG installed into the distribution system is considered.The results are shown that, when DG is installed close to the substation, the electrical line losses are reduced.However, if DG capacity becomes larger and the distance between DG and load is longer, the electrical line losses tend to increase.The results of this paper can be used to create the suitability and fairness of the fee for both DG and utility.
Keywords: Line (geometry); Optimal Power Flow Distribution